Economia Circular em Belo Horizonte: análise do município, políticas e intervenientes, sob a ótica de uma cidade circular - Parreira, Leandro Schneider Alves (2023)
Humanity is experiencing turbulent times, caused by the effects of global warming and climate change. Such phenomena reverberate in different socioeconomic spheres, demanding that society search for new means of existence, which are more sustainable and respect the Earth's natural limits. In this sense, the current economic model, called Linear Economy, has been, since its origin, harmful to the environment, as it is based on the massive extraction of virgin raw materials, the production, in general, of non-eco-efficient products, rarely designed to be reused or repurposed, and, finally, in planned obsolescence and inadequate disposal, generating waste that is barely recycled or reused. A counterpoint to the linear economic model, the Circular Economy can contribute to placing humanity on a safe and fair level for everyone, combining concern with the Earth's ecological ceiling and the presence of a social foundation. It is a concept that associates economic development with better use of natural resources, through new business models and optimization of manufacturing processes. The expansion of this circular model and its applicability in the urban context gave rise to the term circular city. Circular cities are municipalities where, together with stakeholders, we seek to apply the concepts of circular economy, improving environmental, economic, and social indicators, increasing the city's resilience and longevity, as well as the well-being of citizens. Aiming to explore the application of concepts in the urban environment, specifically in the city of Belo Horizonte, this work's central objective is to analyze the capital of Minas Gerais through the lens of a circular city. Therefore, a narrative review of convenience is used, in order to present the concepts of Circular Economy and Circular City. Next, a chapter is dedicated to the analysis of the cities of Amsterdam, in the Netherlands, and Paris, in France, in the context of Circular Cities. It continues with a chapter that addresses the panorama of the Circular Economy and waste management in Brazil. The penultimate chapter analyzes socio-economic-environmental indicators of Belo Horizonte, related to the theme of Circular Economy, comparing the capital of Minas Gerais with other Brazilian capitals and cities. The last chapter delves into BH's municipal policies and plans, related to the Circular Economy, using document and content analysis, field work, forms, questionnaires, and semi-structured interviews with stakeholders. It is observed that, although Belo Horizonte is not a city in transition to the circular model, it presents solid strategies related to the topic and good reach in some key indicators in the evaluation of circular cities. On the other hand, barriers to the materialization of plans include low integration between government sectors, a lack of political and societal interest in the environmental agenda, interference from the business sector and operational and financial bottlenecks.